 #1
 179
 4
Here's the proof that I read for method of variation of parameters
https://www.physicsforums.com/attachment.php?attachmentid=52267&stc=1&d=1351081780
What I couldn't understand is that how could one simply assume that
u'_{1}y_{1}+u_{2}'y_{2}=0 and
u'_{1}y'_{1}+u_{2}'y'_{2}=g(x)
I just don't understand from where you get those above two results.
I would be really happy if could clear my doubt.
Thanks a lot for physics forum and its members. You have helped me a lot :)
https://www.physicsforums.com/attachment.php?attachmentid=52267&stc=1&d=1351081780
What I couldn't understand is that how could one simply assume that
u'_{1}y_{1}+u_{2}'y_{2}=0 and
u'_{1}y'_{1}+u_{2}'y'_{2}=g(x)
I just don't understand from where you get those above two results.
I would be really happy if could clear my doubt.
Thanks a lot for physics forum and its members. You have helped me a lot :)
Attachments

15 KB Views: 667